Ironic effect on emotional response and attitude: moderating role of incongruity degree. - Gu, junwen (2020)
This dissertation probed the relationship between degree of incongruity, emotional response and attitude in an advertising context based on Mandler’s (1982) schema incongruity theory. The schema incongruity theory has been studied by psychologists to explain how it evokes people’s extra psychological efforts to produce satisfaction feelings after finishing the resolution by reconciling the inconsistency between the incongruent message they are exposured and the original schema. This theory is also contributed to the field of advertising research as it could assist advertisers to forecast how consumers would utilize the schema incongruity to process and assess their advertisings and brands. Additionally, as three components of affective factors in advertising context, attitude towards the advertising (Aad), attitude towards the brand (Ab) plus emotional response are crucial determinants for advertising success. However, the measurement of emotional response in previous schema incongruity researches was always twisted its role by adopting the insufficient cognitive measures to evaluate emotions. Typical problems such as wrongly recognize the conception of “affect” or “attitude” as emotional response, fail to distinct respondents’ emotional responses changes generated by different levels of incongruity or only measure the comparison between the congruent and extremely incongruent situation neglecting the role of moderate incongruity degree.